Doping Knowledge Among Indonesian Athletes: Sociodemographic Correlates and Educational Implications (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
A vital defense against rule infractions that could endanger athletes' careers and the integrity of sport is doping knowledge. The purpose of this study was to evaluate Indonesian athletes' knowledge of doping and investigate how it relates to sociodemographic traits. A cross-sectional quantitative survey was completed by 436 athletes from different sports disciplines. Four knowledge domains were covered by the instrument: national anti-doping organizations, legal regulations, prohibited substances, and the definition of doping. The findings showed that athletes were generally aware of the existence of anti-doping organizations and the idea of doping. Nonetheless, there were still a lot of common misconceptions about prohibited substances. Many respondents believed that therapeutic-use drugs such as insulin and erythropoietin (EPO) were unrestricted, or they confused legal supplements with doping. While no significant differences were observed by gender, sport type, competition level, or medal achievement, knowledge varied significantly by age (p = 0.001), student status (p = 0.001), and athletic experience (p = 0.011). These findings highlight the need for more contextualized, practice-oriented anti-doping education tailored to athletes’ backgrounds. Strengthening evidence-based education may foster a cleaner and more ethical sporting environment in Indonesia.